Real-world effectiveness of BNT162b2 mRNA vaccine: a meta-analysis of large observational studies - Kow, Chia Siang (Inflammopharmacology, 2021)
This paper aims to summarize through meta-analyses the overall vaccine effectiveness of the BNT162b2 mRNA vaccine from observational studies. A systematic literature search with no language restriction was performed in electronic databases to identify eligible observational studies which reported the adjusted effectiveness of the BNT162b2 mRNA vaccine to prevent RT-PCR confirmed COVID-19. Meta-analyses with the random-effects model were used to calculate the pooled hazard ratio (HR) and pooled incidence rate ratio (IRR) at 95% confidence intervals, and the vaccine effectiveness was indicated as (pooled HR − 1)/HR or (pooled IRR − 1)/IRR. Nineteen studies were included for this meta-analysis. The meta-analysis revealed significant protective effect against RT-PCR confirmed COVID-19 ≥ 14 days after the first dose, with vaccine effectiveness of 53% (95% confidence interval 32–68%), and ≥ 7 days after the second dose, with vaccine effectiveness of 95% (95% confidence interval: 96–97%). Despite its effectiveness, reporting vaccine safety data by relevant stakeholders should be encouraged as BNT162b2 mRNA is a new vaccine that has not gained full approval. There have been limited data about vaccine effectiveness among immunocompromised patients; thus, the vaccine should be used cautiously in this patient population.